2010
DOI: 10.18352/ijc.178
|View full text |Cite
|
Sign up to set email alerts
|

Fisheries co-management institutions in Southern Africa: A hierarchical analysis of perceptions of effectiveness

Abstract: A random sample attitude survey concluded a ten-year research effort on fisheries co-management that was carried out in Malawi, Mozambique and Zambia. The survey responses were analysed using a two-level hierarchical model that allowed conclusions about village-level institutions to be based on individuallevel survey responses. The present paper describes the surveys background, methodology, and conclusions. Three of these conclusions are very clear from the survey results. The first is that co-management that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…See [26] for details about the evolution of the TACCs. 13 The South American programs share a top-down design and enforcement that is intended to protect commercial fisheries in danger of resource collapse [31,32]. Most recently, in 2008, Peru implemented IVQs for its anchovy stocks, which is one of the largest fisheries in the world in terms of volume.…”
Section: Latin America and The Caribbeanmentioning
confidence: 99%
See 1 more Smart Citation
“…See [26] for details about the evolution of the TACCs. 13 The South American programs share a top-down design and enforcement that is intended to protect commercial fisheries in danger of resource collapse [31,32]. Most recently, in 2008, Peru implemented IVQs for its anchovy stocks, which is one of the largest fisheries in the world in terms of volume.…”
Section: Latin America and The Caribbeanmentioning
confidence: 99%
“…At the same time, research on overcoming the common pool resources (CPR) problem in developing world fisheries often focuses on co-managed fisheries [10][11][12][13], where a co-managed fishery is defined as a fishery with the resource user group and a governing entity both sharing responsibility and authority over the fishery. Although co-managed fisheries can allocate property rights to resource users, property rights are not essential.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the penalties that are sanctioned on fishers have not been clearly documented instead they are passed on to fishers orally, leaving fishers with no avenue of questioning their credibility. Wilson et al (2010) suggested that procedures for enforcement, including the use of proceeds from fines and confiscations, should be formal and standard across all national fisheries.…”
Section: Resultsmentioning
confidence: 99%
“…The facilitators should also be held accountable to all stakeholders including the weak ones, if they are to be supported. As alluded to by Wilson et al (2010), co-management programs will be stronger and more likely to succeed if partnerships are made between stakeholders that are seen to be trustworthy, transparent in their operations, and operating cooperatively and equitably.…”
Section: Institutional Collaborations Trust and Accountabilitymentioning
confidence: 99%